(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2023)
This paper explores the utilization and significance of social media in advancing eco- friendly tourism among the Millennial demographic amidst the challenges posed by the global COVID-19 pandemic. Reviving green tourism during this period presents a notable challenge for the industry, prompting the implementation of various marketing strategies aimed at engaging Millennials in sustainable travel practices. Social media emerges as a pivotal tool in raising awareness and fostering green tourism among Millennials, demonstrating its effectiveness in driving positive outcomes for sustainable tourism initiatives. Thus, this paper offers insights into the crucial role played by social media in promoting eco friendly tourism among Millennials and facilitating informed decision-making for sustainable travel experiences.